PENGARUH MOTIVASI KERJA DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT TAT TWAM ASI (SPBU) JAKARTA SELATAN - Peri Muradi; Sudiarto (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the effect of work motivation and workload on employee job satisfaction at PT Tat Twam Asi (SPBU) South Jakarta. The method used is quantitative. The sampling technique used saturated sampling, namely 54 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that work motivation has a positive significant effect on employee job satisfaction with a coefficient of determination value of 41.7% and the hypothesis test obtained t count > t table or (6.100 > 2.007). Workload has a negative significant effect on employee job satisfaction with a coefficient of determination value of 22.3% and hypothesis testing obtained t count > t table or (-3.862 > -2.007). Work motivation and workload simultaneously have a significant effect on employee job satisfaction with the regression equation Y = 26.783 + 0.489X1 - 0.174X2. The coefficient of determination value is 58.1% while the remaining 41.9% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (35.398 > 2.790).